2017
DOI: 10.1080/02670844.2017.1317452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cryogenic treatment on tribological behaviour of TiC composite coatings

Abstract: Plasma transferred arc (PTA) welding methods were used to produce titanium carbide (TiC) composite coating layers on the surface of 38MnVS6 steel and subsequently deep cryogenic treatment (DCT) was applied to the PTA coating layers. The effects of the TiC powder, different energy inputs (100 and 120A), and DCT on the microstructure and tribological performance were investigated. The microstructure of the composite coatings consisted of cubic TiC, unmelted TiC, and iron matrix. The alloyed and cryogenic treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Unfortunately, Gill et al [22] have discovered that DCT weakens the interfacial adhesion bonding of TiAlN coating and tungsten carbide substrate, leading to a destructive effect on the machining performance, especially at lower cutting speeds. Moreover, as reported in other literatures [19,20,24], the DCT does not always improve the wear performance of coatings/films. Thus, it can be inferred that the different property with DCT is closely related to the intrinsic physical characteristics of different coating/film and substrate as well as the different preparation parameters with different technology.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Unfortunately, Gill et al [22] have discovered that DCT weakens the interfacial adhesion bonding of TiAlN coating and tungsten carbide substrate, leading to a destructive effect on the machining performance, especially at lower cutting speeds. Moreover, as reported in other literatures [19,20,24], the DCT does not always improve the wear performance of coatings/films. Thus, it can be inferred that the different property with DCT is closely related to the intrinsic physical characteristics of different coating/film and substrate as well as the different preparation parameters with different technology.…”
Section: Introductionsupporting
confidence: 54%
“…To our knowledge, by DCT, the service performance of the coating/film can be also abstractly improved, to a certain extent. However, based on the website of web of science (http://isiknowledge.com), a few studies concerning the influence of DCT on coating/film have been reported [19][20][21][22][23]. Therefore, it is necessary to continue the research of DCT on the coating/film for driving its practical application.…”
Section: Introductionmentioning
confidence: 99%
“…They reported increased in hardness about 5times and wear resistance about 2.5times. Kılıçay et al [15] examined TiC composite coatings on 38MnVS6 for tribological behaviour in micro alloyed steel continuous with cryogenic cooling. They obtained decreased coefficient of friction (COF) and wear rate.…”
Section: Various Alloy Materials Used For Claddingmentioning
confidence: 99%